(untitled) (World Economics and Finance Bulletin, 2024)
The chemical industry plays a crucial role in the global economy, supplying essential materials for various sectors, including manufacturing, pharmaceuticals, agriculture, and consumer goods. Given its significance, a comprehensive evaluation of the chemical industry is vital to ensure sustainability, safety, and compliance with regulatory requirements. This article explores the criteria and indicators used for a thorough assessment of the effectiveness and impact of digitization in the chemical industry